The enduring library : technology, tradition, and the quest for balance - Gorman, Michael, 1941- (American Library Association, 2003)
Librarians are experts at selecting, evaluating, and disseminating the best content in the most appropriate format to meet the needs of library users. And, new technologies can be invaluable tools in these efforts. Taking advantage of these technologies does not, however, change the fundamental mission of libraries everywhere. In this thought-provoking work, one of the library world's leading thinkers discusses the transformative effect communications technology has had on information delivery from past to present to future. By tracing the transformations, Gorman writes a roadmap for achieving.